The cost of diversity the diversification discount and inefficient investment - Rajan, Raghuram Govind 1963-; Servaes, Henri; Zingales, Luigi 1963- (1998)
In a simple model of capital budgeting in a diversified firm where headquarters has limited power, we show that funds are allocated towards the most inefficient divisions. The distortion is greater the more diverse are the investment opportunities of the firm's divisions. We test these implications on a panel of diversified firms in the U.S. during the period 1979-1993. We find that i) diversified firms mis-allocate investment funds; ii) the extent of mis-allocation is positively related to the diversity of the investment opportunities across divisions; iii) the discount at which these diversified firms trade is positively related to the extent of the investment mis-allocation and to the diversity of the investment opportunities across divisions.
Keywords: Allocation de ressources - Modèles économétriques; Budget d'investissement - Modèles économétriques; Diversification (économie politique) - États-Unis - Modèles économétriques; Investissements de capitaux - États-Unis - Modèles économétriques; Ökonometrisches Modell; Capital budget -- Econometric models; Capital investments -- United States -- Econometric models; Diversification in industry -- United States -- Econometric models; Resource allocation -- Econometric models; Mischkonzern; Diversifikation; Investitionsrechnung; USA